Teacher Development through a Training System in Central Aceh District - Alfi Syahril Fuadi Jaya; T.M Jamil; Syafira Fitri (Proceedings of AICS - Social Sciences, 2021)
The purpose of this study is to find out the teacher development system through training on teacher professional and pedagogic competencies and the outcomes (outcomes) of the teacher training system through training by the Central Aceh District Education Office. This research approach is qualitative and the type of descriptive research. Data was collected by using interview, observation and documentation studies. The subjects of this study were informants from the Central Aceh District Education Office. Data analysis used techniques in qualitative research consisting of data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate that the teacher development system through training in Central Aceh Regency already has an integrated system, meaning that it is related to one system to another, starting with planning, implementing, and evaluating training for junior high school teachers. The measurement of the effectiveness of the results of teacher coaching through training is evidenced by the results of the Teacher Competency Test (UKG) scores, especially teachers. The improvement of teacher competence in teaching has shown a positive direction where teachers have shown creativity and innovation during the learning process. However, the obstacles faced by the Central Aceh District Education Office are that some teachers have low motivation in participating in training and the lack of teachers’ skills in the field of ICT (Information, Communication and Technology).Keywords: System, coaching, teachers, training.